PROGRAM PEMBINAAN DAN EVALUASI PRESTASI OLAHRAGA KHUSUSNYA BOLA VOLI PADA SMK NEGERI DI KOTA SIGLI - Sumarjo, Sumarjo (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2024)
This study aimed to provide a comprehensive analysis of the assessment of the effectiveness of the Volleyball Training Programme at a Vocational School in Sigli City. This study focuses on trainers, coaches, and players from SMKN 1 and SMKN 3 in Kota Sigli. The study utilizes a validated questionnaire as the data-gathering instrument. The analysis of this study employed qualitative data analysis and statistical data validation through the use of percentages. The findings of this study indicate that the volleyball training program at the vocational school in Sigli City has not yet achieved optimal results in its execution. Out of the two schools that were examined, only one school effectively implements the development program. The inadequate management of buildings and infrastructure, the delayed distribution of funding for the development program, and the insufficient support from the school were all evident. The absence of a comprehensive training program provided by coaches hinders the successful implementation of the peak achievement program. The study concludes that the development program is experiencing poor management of facilities and infrastructures, namely within the school's management. Out of the two schools that were studied, only 25% had successfully executed the development program.Keywords : Achievement Training Program, Evaluation, Volley Ball